Клинико-иммунологические сопоставления у больных псориазом с хронической вирусной инфекцией = Clinical and immunological comparison in psoriasis patients with chronic viral infection - Procenko, T. V.; Ziablitsev, S. V.; Bohatyrova, I. N. (Journal of Education, Health and Sport, 2015)
Procenko T., Ziablitsev S., Bohatyrova I. Клинико-иммунологические сопоставления у больных псориазом с хронической вирусной инфекцией = Clinical and immunological comparison in psoriasis patients with chronic viral infection. Journal of Education, Health and Sport. 2015;5(4):299-308. ISSN 2391-8306. DOI: 10.5281/zenodo.17149 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A299-308 https://pbn.nauka.gov.pl/works/555206 http://dx.doi.org/10.5281/zenodo.17149 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 10.04.2015. КЛИНИКО-ИММУНОЛОГИЧЕСКИЕ СОПОСТАВЛЕНИЯ У БОЛЬНЫХ ПСОРИАЗОМ С ХРОНИЧЕСКОЙ ВИРУСНОЙ ИНФЕКЦИЕЙ CLINICAL AND IMMUNOLOGICAL COMPARISON IN PSORIASIS PATIENTS WITH CHRONIC VIRAL INFECTION Т. В. Проценко, С. В. Зяблицев, И. Н. Богатырева T. Procenko, S. Ziablitsev, I. Bohatyrova Донецкий национальный медицинский университет им. М. Горького Donetsk National Medical University Abstract Investigated inetrleukines I L1β, IL6, IL8 and allelic polymorphism of the genes IL-1β, TLR-2, MTHFR 40 psoriasis patients with and without chronic herpes virus infection (HWI): cytomegalovirus (CMV), Epstein-Barr virus(immune-EBV). In psoriasis patients, in comparison with the control group showed an increase level of IL8, IL6 and IL1b. Shown a statistically significant relationship between level IL1b polymorphism with C-31T IL1b gene is most expressed when the genotype T/T. The dependence of the level of IL1b from allelic polymorphism of TLR-2 (Arg753Gln), most pronounced in psoriasis patients with homozygous genotype Arg/Arg. Multivariate mathematical analysis showed a statistically significant difference in the level IL1b allelic polymorphism of TLR-2 (Arg753Gln), most pronounced in patients with psoriasis with HWI. It is set by the construction of logistic model, that risk of heavy and heavy flow of dermatosis higher for women, and increased with age and for men and for women, related to the level of IL6 and allelic polymorphism of Glu429Ala of gene of MTHFR (model sensitiveness 95,8 %, 95 % ДИ 78,9 % - 99,9 %; specificity is 71,4 %, 95 % ДИ 29,0 % - 96,3 %), statistically meaningfully higher in patients by psoriasis with HWI at the genotype of Arg/Arg gene of TLR - 2. Key words: psoriasis, interleukins, genetic polymorphism, chronic viral infection, cytomegalovirus, Epstein-Barr virus. Резюме Исследованы инетрлейкины IL1β, IL6, IL8 и аллельный полиморфизм генов ИЛ-1β, TLR-2, MTHFRу 40 больных псориазом с наличием и без хронической герпесвирусной инфекции (ХВИ): цитомегаловирусной (ЦМВ), Эпштейн-Барр-вирусной(ЭБВ).У больных псориазом,в сравнение с контрольной группой установлено повышение уровня IL8, IL6 и IL1b. Показана статистически значимая связь уровня IL1b с полиморфизмом C-31T гена IL1b, наиболее выраженная при генотипе Т/Т. Выявлена зависимость уровня IL1b от аллельного полиморфизма гена TLR-2 (Arg753Gln), наиболее выраженная у больных псориазом с гомозиготным генотипом Arg/Arg. Многофакторный математический анализ показал статистически значимое различие уровня IL1bи аллельного полиморфизма гена TLR-2 (Arg753Gln), наиболее выраженное у больных псориазом с ХВИ. Путем построения логистической модели установлено, что риск среднетяжелого и тяжелого течения дерматоза выше у женщин, и повышался с возрастом и у мужчин и у женщин, связан с уровнем IL6 и аллельным полиморфизмом Glu429Ala гена MTHFR (чувствительность модели 95,8 %, 95 % ДИ 78,9 % – 99,9 %; специфичность – 71,4 %, 95 % ДИ 29,0 % – 96,3 %), статистически значимо выше у больных псориазом с ХВИ при генотипе Arg/Arg гена TLR-2. Ключевые слова: псориаз, интерлейкины, полиморфизм генов, хроническая вирусная инфекция, цитомегаловирус, Эпштейн-Барра вирус.